Aplikasi Absensi DP3A Kabupaten Nabire Provinsi Papua Tengah Berbasis Web menggunakan Metode RAD - Cici Kamalia; Novela Raubaba (Jurnal Teknologi dan Informatika, 2026)
The Women's Empowerment and Child Protection Office (DP3A) of Nabire Regency, Central Papua Province, faces various obstacles in recording employee attendance that was previously done manually, such as recording errors, delays in reporting, and difficulties in data recap. To overcome these problems, a web-based attendance application was developed using the Rapid Application Development (RAD) method. This method includes the stages of needs planning, prototyping, iterative system development, and continuous implementation and evaluation. The RAD approach enables fast, flexible, and responsive application development to user needs, by actively involving staff in the process of testing and refining the system. The test results show that the app is able to record attendance in person, generate accurate reports, and support staff data management in a more regular and transparent manner. Thus, this web-based attendance application is expected to improve operational efficiency, strengthen accountability, and support better administrative governance in the DP3A environment of Nabire Regency.